National, disciplinary and temporal variations in the extent to which articles with more authors have more impact: Evidence from a geometric field normalised citation indicator - Sud, Pardeep (2015)
The importance of collaboration in research is widely accepted, as is the fact that articles with more authors tend to be more cited. Nevertheless, although previous studies have investigated whether the apparent advantage of collaboration varies by country, discipline, and number of co-authors, this study introduces a more fine-grained method to identify differences: the geometric Mean Normalized Citation Score (gMNCS). Based on comparisons between disciplines, years and countries for two million journal articles, the average citation impact of articles increases with the number of authors, even when international collaboration is excluded. This apparent advantage of collaboration varies substantially by discipline and country and changes a little over time. Against the trend, however, in Russia solo articles have more impact. Across the four broad disciplines examined, collaboration had by far the strongest association with impact in the arts and humanities. Although international comparisons are limited by the availability of systematic data for author country affiliations, the new indicator is the most precise yet and can give statistical evidence rather than estimates.Comment: Thelwall, M., & Sud, P. (in press). National, disciplinary and temporal variations in the extent to which articles with more authors have more impact: Evidence from a geometric field normalised citation indicator. Journal of Informetric